Increasing the radioiodine dose does not improve cure rates in severe Graves’ hyperthyroidism : a clinical trial with historical control - Dora, José Miguel Silva (2015)
Objective. It is generally accepted that higher doses of radioiodine (131I) improve cure rates in Graves’ disease (GD). In this trial we sought to evaluate whether very high 131I doses increase the efficacy of treatment in severe GD. Design. Clinical trial with historical control. Patients with GD and a goiter ≥48mL were eligible for the study. The patients in the contemporaneous intervention cohort were treated with 250Ci of 131I/mL thyroid tissue, corrected by 24-RAIU values (Group 1; = 15). A subgroup of patients with GD and a goiter ≥48mL who were treated with 200 Ci of 131I/mL/24-RAIU in a previously published randomized controlled trial served as a historical control group (Group 2; = 15). The primary outcome evaluated was the one-year cure rate. Results. There were no significant baseline differences regarding age, gender, body mass index, smoking status, pretreatment with methimazole, thyroid volume, or thyroid hormone levels of the two treatment groups.The cumulative 12-month cure rate for the patients in Group 1 was 66.6%, a figure similar to the 12-month cure rate observed in Group 2 (60.0%; = 0.99). Conclusions. Our results suggest that increasing the 131I dose does not improve cure rates in severe GD.This trial is registered with ClinicalTrials.gov NCT01039818.